Molecular Epidemiological, Serological, and Pathogenic Analysis of EV-B75 Associated With Acute Flaccid Paralysis Cases in Tibet, China - Zhang, Keyi; Hong, Mei; Zhang, Yong; Han, Zhenzhi; Xiao, Jinbo; Lu, Huanhuan; Song, Yang; Yan, Dongmei; Wang, Dongyan; Zhu, Shuangli; Xu, Wenbo; Wu, Guizhen (Frontiers in Microbiology, 2021)
Enterovirus B75 (EV-B75) is a newly identified serotype of the enterovirus B species. To date, only 112 cases related to EV-B75 have been reported worldwide, and research on EV-B75 is still limited with only two full-length genome sequences available in GenBank. The present study reported seven EV-B75 sequences from a child with acute flaccid paralysis and six asymptomatic close contacts in Shigatse, Tibet. Phylogenetic analysis revealed that the Tibetan strain was possibly imported from neighbouring India. Seroepidemiological analyses indicated that EV-B75 has not yet caused a large-scale epidemic in Tibet. Similarity plots and boot scanning analyses revealed frequent intertypic recombination in the non-structural region of all seven Tibet EV-B75 strains. All seven Tibetan strains were temperature-sensitive, suggesting their poor transmissibility in the environment. Overall, though the seven Tibetan strains did not cause large-scale infection, prevention and control of the novel enterovirus cannot be underestimated.